P156 Does analysis of patient-ventilator interaction offer benefits in addition to overnight pulse oximetry in patients with motor neurone disease being followed on non-invasive ventilation?. (16th November 2010) - Chakrabarti, B; Ando, H; Thornton, E; Ford, V; Young, C A; Angus, R M
Abstract : Introduction: Non-invasiveventilation (NIV) is increasingly being offered to Motor Neurone Disease (MND) patients as studies report benefit insurvival and quality of life (QoL). Ventilator technology allows monitoring of patient–ventilator interaction. It is less clear whether such data yield useful additional information over pulse overnight oximetry. In a longitudinal study, MND patients were assessed both physiologically and psychologically prior to NIV initiation and 3monthly until death. Methods: 35 patients were enrolled; 28 offered NIV; 11 declined and 17 established on treatment. At initiation all had nocturnal hypoventilation by symptoms andoximetry criteria. Nine patients (8 male; median age 60 years) had ≥12 months follow-up on ventilation; none required oxygen with NIV. Patient–ventilator interaction was assessed by analysis of the 'memory card' from the ventilator at 4–6 months post initiation (Point A) and at 10–12 months (Point B); QoL assessed by validated questionnaires within 2 weeks of memory card analysis. Results: Median overnight oxygen saturation in the sample was 93% at point A and 94% at B; only 3 and 2 patients respectively exhibited 'sub-optimal' oximetry that is, >30 min below 90% saturation resulting in adjustment of ventilation. Minute Ventilation (MV) fell in the group from Point A to B (mean 6.97–6.34 l/min); a fall in MV (noted in five patients of which 1 exhibited "sub-optimal" oximetry) was associated with a fall in ALS FRS score denoting worsening health status (correlation coefficient 0.73; p=0.026). Ventilator triggering decreased overall in the group from Points A to B (mean 69.95–61.57% proportion of triggered breaths); a decrease in ventilator triggering (noted in six patients of which 1 exhibited "sub-optimal" oximetry) correlated with an increase in ALS AQ domain for emotion denoting worsening emotional functioning (correlation coefficient −0.89; p=0.002) with anon-significant trend noted between fall in triggered breaths and increase in Hospital Anxiety and Depression (HAD) score (correlation coefficient −0.68; p=0.055). Conclusion: In MND, monitoring of patient–ventilator interaction may serve as a useful adjunct to pulse oximetry and symptom assessment. Further studies are needed to ascertain whether adjustment of ventilation based on this approach allows patients to gain full benefit from NIV.